PROFIL KEKERASAN ORANG TUA PADA ANAK DI KAMPUNG LUBUK BANGKA NAGARI IV KOTO MUDIEK KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Anggraini, Rizki Rani (Bimbingan dan Konseling, 2014)
This research was bosed of image violences parents from physical and psychological to the child in the village of Lubuk Bangka IV Nagari Koto Mudiek District of Batang Kapas. Based on observations and interviews the researchers found a there was still parents who abuse to child physical and psychological. The focus of this research was the profile of parents violence in physical and psychological. This to child qualitative descriptive that describe, a facts and reality in the field. The research informants selected based on certain criteria, a key informants were parents (Mother) by 2 persons and an additional a father, children, neighbors and friends as many as 8 persons. This data was tested by doing triangulation and conduct of member checks , then analyzed using a 3 steps: 1. Data of reduction, 2. Data of presentation, 3. Withdrawal of conclusion. The results showed that: (1) The profile of violences physical, still less in accordance with its role as the parents that should give love to children and protect them, (2) The profile of violences psychological, the parents were still unaware that emotional hardness done to children a good conscious or unconscious bad impact on children. Based on the results of research was recommended to parents and concerned parties can educate children to refrain from hardness, but with firmness, affection and tenderness in children.